Optimizing Student Development through Effective Assessment Practices: Insights from School Counselors in Indonesia - Jumail, Jumail; Laisouw, Yusup; Mahaly, Sawal; Maswain, Maudianti (Jurnal Bimbingan dan Konseling Terapan, 2024)
Since the advent of the Industrial Revolution 4.0, education has gained significant attention from academics and practitioners. The transformative initiatives introduced by Indonesia's Minister of Education and Culture, Nadiem Makarim, have reshaped the educational landscape, particularly through the "Merdeka Belajar" (Freedom to Learn) program. This qualitative study, utilizing a descriptive approach, investigates the use of assessments by school counselors (BK teachers) and their implementation in guidance and counseling services. The research involved 11 informants, including school principals, BK teachers, and students, selected through purposive sampling. Data were collected using observations, interviews, and documentation, and analyzed following Miles & Huberman's methodology. Findings reveal that while BK teachers follow structured steps in using assessments, they face challenges such as the lack of standardized instruments, limited time, and inadequate technological integration. Despite these obstacles, BK teachers strive to improve their practices by effectively communicating assessment results, integrating technology, and implementing actionable insights. The study underscores the necessity for better resources and applications to support the effective use of assessments. Assessments are crucial for understanding students' strengths and needs, providing tailored guidance, and facilitating academic, social, and emotional development. This data-driven approach enhances early problem identification, informed interventions, and the development of students' unique potentials. The study concludes that effective assessment implementation, supported by a positive school environment and adequate resources, is vital for enhancing the quality of guidance and counseling services, ultimately contributing to improved educational outcomes and student well-being.